Reason for Reserve? Reserve Requirements and Credit. Issue 2 (March 2014) - MORA, NADA
<x xml:space="preserve">Abstract</x> This paper considers the impact of a regulatory policy action on bank credit and traces its incidence across banks. I make use of a reserve requirement increase in Lebanon that was considerably greater on foreign currency deposits than on domestic currency deposits. All banks cut lending as they scrambled to adjust portfolios. But the policy shock disproportionately affected banks with a greater reliance on dollar funding and with low buffers of dollar liquid assets. Exposed domestic‐owned banks also adjusted more slowly than similar foreign‐owned banks that obtained outside funding. Descriptive firm–bank matching evidence reveals a disproportionate impact on small firms.